Identity Crisis: Stagnation During Adulthood in Breaking Bad by Vince Gilligan - Muhamad Afri Arya Dilla; Latifah Latifah (Lembaga Pengembangan Kinerja Dosen, 2026)
The study is entitled “Identity Crisis: Stagnation During Adulthood in Breaking Bad by Vince Gilligan (2008)”. This study aims to analyze the phenomena of identity crisis at stages of stagnation during adulthood which is experience by Walter White as the protagonist in Breaking Bad during his late 40’s. when he diagnosed by cancer, he had to survive in order to provide his family by selling drugs using his skill in chemistry before he passed away. Moreover, the study has two main objects which are first describing the phenomena of identity crisis, and second how does the protagonist response with identity crisis. In addition, the qualitative method will be used in order to analyze the phenomena of identity crisis by providing several dialogs and scenes from the film. Furthermore, this study applies the theory by Erik Erikson in (1982) of identity crisis in his book The Life Cycle Completed at the stage of stagnation which later on answering the research objects. The results of this study indicates that the protagonist challenges an identity crisis at stages of stagnation which leads to a sense of unproductive and uninvolved while the protagonist lack of generative matters for his family. On the other hand, the protagonist deals the crisis by using procreativity in chemistry, and productive which is engaging in a positive impact by providing his family which leads to generativity and successful in this stage.